Blue Bison needs a haircut - Rothman, Scott (Random House Studio, 2022)
Blue Bison prides himself on always looking clean and neat, so when he goes for a haircut and discovers everyplace is closed, he is very upset, but his little sister Bubble Gum Bison and her utterly ridiculous idea saves the day.